An unusual branching pattern of the median cubital vein and its relations with lateral cutaneous nerve of forearm in the upper extremity: anatomicoclinical notes. - Mona S,; Ranjeeta H,; Vandana M,; Jyoti A,; Rajesh S,; Gayatri R, (Department of Surgery, UKM Medical Centre, 2014)
Cubital fossa is the usual site for performing venepuncture in the clinical settings for health screenings and diagnostic purposes. This procedure is simple and uncomplicated but occasionally can lead to bleeding and pain in the form of complex regional pain syndrome. Superficial veins of the upper limb are often used for venepuncture for transfusion purposes and for obtaining blood samples. These veins are also used for cardiac catheterisation and giving intravenous injections. During routine cadaveric dissection, a cubital venous variation was observed in a 45-yr –old, male cadaver. The median cubital vein initiated from cephalic vein passed upwards and laterally superficial to posterior branch of medial cutaneous nerve of forearm. In the middle of its course, it gave off an ascending channel which further divided into medial and lateral tributaries. The medial tributary terminated into the basilic vein, whereas the lateral tributary ascended laterally superficial to a branch of lateral cutaneous nerve of forearm and drained into cephalic vein at the level of elbow joint. Various patterns of superficial cubital veins have been mentioned in literature. Awareness of such anatomical variations is crucial while performing venepuncture in clinical settings as well as for creating arteriovenous fistulas for hemodialysis purpose.